Cinema at the End of Empire A Politics of Transition in Britain and India - Jaikumar, Priya (Duke University Press, 2005)
How did the imperial logic underlying British and Indian film policy change with the British Empire's loss of moral authority and political cohesion? Were British and Indian films of the 1930s and 1940s responsive to and responsible for such shifts? Cinema at the End of Empire illuminates this intertwined history of British and Indian cinema in the late colonial period. Challenging the rubric of national cinemas that dominates film studies, Priya Jaikumar contends that film aesthetics and film regulations were linked expressions of radical political transformations in a declining British empire and a nascent Indian nation. As she demonstrates, efforts to entice colonial film markets shaped Britain's national film policies, and Indian responses to these initiatives altered the limits of colonial power in India.